Book Review: Wilson, C & Wilson R. (2025). University and You: Strengthening Your Skills and Developing Your Potential - Parker, Virginia (St Andrews Journal of International and Language Education, 2025)
This review presents the book University and You: Strengthening Your Skills and Developing Your Potential, which is a recent publication offering advice to students who may be new to the context of UK-based university study. This review introduces the layout and main foci of this book and offers an evaluation of its utility as a practical guidebook for students taking their first steps into UK higher education.